An Empirical Study of Demographic factors, Neuroticism and Extraversion as Correlates of Psychological Well-being of Police Officers in Lagos State, Nigeria - Akintayo, Samson; Ohanekwu, Emmanuel; Adepoju, Toluwalase; Yakubu, Emmanuel (International Journal of Multidisciplinary Approach Research and Science, 2026)
Psychological well-being (PWB) is a complex, multi-dimensional concept that captures positive functioning and self-perception, life satisfaction beyond the absence of mental illness, emotional resilience and the capacity to cope with life's stressors but often overlooked when it comes to Police Officers as this Organization is an aspect of law enforcement, particularly in challenging contexts like Nigeria. It is against this backdrop that this study investigates the relationships between demographic factors, neuroticism, and extraversion as correlates of psychological well-being (PWB) among police officers in Lagos State, Nigeria. Utilizing a descriptive correlational research design, the study sampled 116 officers from five area commands using simple random sampling techniques. Data were collected using standardized instruments, including Ryff’s Brief Psychological Well-Being Scale (α = 0.86) and an adapted Neuroticism and Extraversion Scale (α = 0.72). Statistical analyses were conducted using t-tests, ANOVA, Pearson’s correlation and multiple regression. The findings revealed no significant gender-based differences in PWB of Police Officers; t(114)= .1.392, p>0.05, significant age-related differences were observed among Police Officers’ PWB; F(2, 113) =3.76, p<0.05. Neuroticism and extraversion emerged as potent predictors of PWB, with neuroticism negatively associated and extraversion positively associated with mental health outcomes. The joint contributions of neuroticism and extraversion accounted for 34.7% of the variance in PWB, underscoring their critical roles in moderating stress and resilience in high-stress professions. The findings recommend among others that interventions to improve PWB should incorporate personality-focused strategies alongside broader systemic reforms. Also, fostering a supportive work environment and reducing stigma around mental health.